Tipologija jezer v Sloveniji - Urbanič, Gorazd (Natura Sloveniae, 2007)
A typology of natural lakes in Slovenia with the surFace area of >50 ha was prepared according to the Water Framework Directive. lake Bled and Lake Bohinjwere taken into consideration only. Both systems proposed by the Water Framework Directive (Directive 2000/60/EC) far the preparation of the lake typology were tested. Using the system A, the satisfactory differentiation forthe description of biological reference conditions could not be established. The system B was chosen based on the obligatory descriptors that include altitude, latitude, longitude, depth, geology and size. An additional descriptor, which concerns bioregional affiliation, was also chosen (sensu Urbanič, 2006a), which includes two obligatory descriptors, altitude and geology. These two descriptors are not specifically mentioned in the description of lake types.
Keywords: hidrologija; jezera; Slovenia; Slovenija; tipologija